The Effect of Orlistat on Sterol Metabolism in Obese Patients - Kwon, Yu-Jin; Kwon, Go Eun; Lee, Hye Sun; Choi, Man Ho; Lee, Ji-Won (Frontiers in Endocrinology, 2022)
Background: Orlistat, a reversible inhibitor of pancreatic and gastric lipase, is known to have anti-obesity and antioxidant properties. Cholesterol intermediates and metabolites have diverse and important functions in cardiovascular disease. Therefore, we aimed to evaluate the effect of orlistat on sterol metabolism in overweight and obese adults after weight loss during the intervention or weight loss at 12 weeks. Methods: A total of 51 (27 in the control group and 24 in the experimental group), patients with a BMI of 27 or greater were randomly assigned in a 1:1 ratio to receive either orlistat (120 mg) three times a day plus phentermine hydrochloride (37.5 mg) once daily or a placebo three times a day plus phentermine hydrochloride (37.5 mg) once daily. The primary study outcome was sterol metabolism. Results: The experimental group exhibited significantly decreased metabolic signatures of serum sterols, free cholesterol, sitosterol, 7α-hydroxycholesterol (7α-OHC), and 7β-OHC at 12 weeks. The experimental group also exhibited significantly decreased metabolic ratios of sitosterol and 7α-OHC to cholesterol at 12 weeks. Regarding changes in sterol signatures from baseline to 6-month follow-up, free cholesterol, plant sterols, and cholesterol precursors tended to decrease with weight loss during the intervention and increase again as the weight was regained in both groups. Conclusion: Orlistat treatment improves oxysterol metabolism in overweight and obese adults. Our findings support that orlistat plays a crucial role in the process of endothelial dysfunction and atherosclerosis via oxysterol modulation.